Use of a warm mix asphalt additive to reduce the production temperatures and to improve the performance of asphalt rubber mixtures - Oliveira, Joel (2013)
Asphalt rubber mixtures are often described as environmentally friendly mixtures due to the incorporation of recycled rubber from used tires and due to their improved service life. In fact, their fatigue cracking and rut resistance properties are better than those of conventional asphalt concrete mixtures. However, asphalt rubber mixtures demand higher production temperatures than conventional mixtures due to the higher viscosity of the asphalt rubber binder. The objective of this paper is to assess the efficiency of using a surfactant based additive in the production of warm mix asphalts, by lowering the mixing temperatures of asphalt rubber and asphalt concrete mixtures without changing their performance. Several laboratory tests were carried out on asphalt rubber and asphalt concrete mixtures, with and without the additive, in order to evaluate and compare the performance of the mixtures. It was concluded that the incorporation of small amounts of a surfactant based additive allowed reducing the production temperatures of both types of mixture by 30 ºC without compromising their performance, and this can be seen as a great step forward towards the production of cleaner asphalt rubber mixtures.